Do Emotions Cause Actions, and If So How?. (October 2017) - Scarantino, Andrea
The main purpose of this article is to consider two of the most popular arguments offered in support of the view that emotions do not cause actions. One argument suggests that emotions come after actions and therefore cannot cause them ( argument from timing ). The other argument suggests that emotions are not necessarily followed by actions and therefore cannot cause them ( argument from imperfect association ). I argue that neither of these two arguments is compelling. At the same time, some of the concerns of causation skeptics can help us better understand what a theory of the causal connection between emotions and actions should explain.